Pharmacological inhibition of FOXO1 promotes lymphatic valve growth in a congenital lymphedema mouse model - Ogunsina, Ololade; Banerjee, Richa; Knauer, Luz A.; Yang, Ying (Frontiers in Cell and Developmental Biology, 2023)
Abstract Mutations in many genes that regulate lymphatic valve development are associated with congenital lymphedema. Oscillatory shear stress (OSS) from lymph provides constant signals for the growth and maintenance of valve cells throughout life. The expression of valve-forming genes in lymphatic endothelial cells (LECs) are upregulated by OSS. The transcription factor FOXO1 represses lymphatic valve formation by inhibiting the expression of these genes, which makes Foxo1 a potential target for treating lymphedema. Here, we tested the ability of a Foxo1 inhibitor, AS1842856, to induce the formation of new lymphatic valves. Our quantitative RT-PCR and western blot data showed that treatment of cultured human LECs with AS1842856 for 48 hours significantly increased the expression levels of valve-forming genes. To investigate the function of AS1842856 in vivo, Foxc2+/- mice, the mouse model for lymphedema-distichiasis, were injected with AS1842856 for two weeks. Valve number in AS treated Foxc2+/- was significantly higher than the vehicle treated Foxc2+/-. Furthermore, since -catenin upregulates the expression of Foxc2 and Prox1 during lymphatic valve formation and AS1842856 treatment increased the level of activated -catenin in both cultured human LECs and in mouse mesenteric LECs in vivo, we used the mouse model with constitutive activated -catenin to rescue loss of lymphatic valves in Foxc2+/- mice. Foxc2+/- mice have 50% fewer lymphatic valves compared to control and rescue experiments showed that valve number was completely restored to the control level upon nuclear -catenin overactivation. These findings indicate that pharmacological inhibition of FOXO1 can be explored as a viable strategy to rescue valve defects in congenital lymphedema.